Fluorescent detection of target proteins via a molecularly imprinted hydrogel. Issue 27 (21st June 2021) - Kubo, Takuya; Watanabe, Naoki; Ikari, Seiji; Liu, Chenchen; Kanao, Eisuke; Naito, Toyohiro; Sano, Tomoharu; Otsuka, Koji
Abstract : A molecularly imprinted hydrogel with a PEG-fluorescent monomer was used for the selective detection of a target protein. Abstract : Proteins are typically separated by an immune reaction, such as an enzyme-linked immunosorbent assay, and are detected by selective fluorescent labeling. This has potential for complicated procedures and the denaturation of proteins by labeling, and is cost consuming. In this study, we propose a technique for the selective separation and detection of a target protein using a molecularly imprinted hydrogel (PI gel) with fluorescent monomers. We focused on 8-anilino-1-naphthalenesulfonic acid (ANS), where the fluorescence intensity is easily changed by the interaction with proteins, and successfully synthesized the ANS monomer and a poly(ethylene glycol) (PEG) conjugated ANS monomer. The PI gel with the ANS monomers using bovine serum albumin (BSA) as a template showed the selective adsorption of BSA and the fluorescence intensity increased due to the adsorption of BSA.